2009
DOI: 10.1097/iae.0b013e3181aa8e20
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injection of Bevacizumab for Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: Intravitreal bevacizumab therapy can be a long-term effective treatment for macular edema secondary to branch retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
69
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 27 publications
11
69
1
1
Order By: Relevance
“…data, 2009] affirm that it is better if associated with grid laser, but we wait for results of other studies to clarify this point. Second, most of the patients needed repeated injections to achieve good results, depending on the different studies [47,48,53,54]; the Pan-American Collaborative Retina Study group showed these high rates of injections in 24 months [48]. Third, there is no defined long-term therapeutic scheme and it is also not known when to start the treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…data, 2009] affirm that it is better if associated with grid laser, but we wait for results of other studies to clarify this point. Second, most of the patients needed repeated injections to achieve good results, depending on the different studies [47,48,53,54]; the Pan-American Collaborative Retina Study group showed these high rates of injections in 24 months [48]. Third, there is no defined long-term therapeutic scheme and it is also not known when to start the treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…They are also useful to reduce ischemic progression and to manage complications, such as neovascular glaucoma [61]. There are some prognostic factors for better outcome, such as better initial VA, no foveal hemorrhages, no macular ischemia, detection of VA gain after first injection, young age and final central retinal thickness [45,48,62,63]. But there are limits in efficacy, need for multiple injections, rebound effect of macular edema and nonresponders.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment options for BRVO include grid laser treatment, intravitreal injection of steroids, surgical procedures and off-label treatment with intravitreal anti-vascular endothelial growth factor (VEGF) agents [1,2]. In recent years, intravitreal anti-VEGF treatment with bevacizumab has been shown to efficiently reduce macular edema and improve visual acuity in numerous case series and prospective or retrospective studies [3,4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%